Impact of repurposed drugs on the symptomatic COVID-19 patients - Iqbal Hussain; Afzal Hussain; Mohamed F. Alajmi; Md. Tabish Rehman; Samira Amir (Elsevier, 2021)
An outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus capable of causing coronavirus disease 2019 (COVID-19), was declared as a global public health emergency on January 30, 2020, by the World Health Organization. In this devastating situation, precautionary measures, early diagnosis, and repurposed drugs appear to be timely and decisive factors by which to handle this problem until the discovery of an effective, dedicated vaccine or medicine is made. Currently, some researchers and clinicians have claimed evidence exists in favor of the use of some antimalarial drugs (chloroquine, hydroxychloroquine) antiviral drugs (remdesivir, favipiravir, lopinavir, ritonavir, umifenovir) vitamins, traditional Chinese medicines, and herbal medicines against SARS-CoV-2 infection. Based on the available literature, this review article sought to highlight the current understanding of the origin, transmission, diagnosis, precautionary measures, infection and drug action mechanisms, therapeutic role, and toxicities of targeted drugs for the prevention and cure of COVID-19. This review may be useful for developing further strategies as a blueprint and understanding the mentioned drugs' mechanisms to elucidate the possible target of action by which to successfully freeze the replication of the SARS-CoV-2 virus.